Juridical Analysis of Digital Transformation in Public Healthcare Services: Towards an Inclusive Health System (Open Society Conference, 2025)
Digital transformation in public healthcare services is a response to the growing need for efficiency, accessibility, and quality in healthcare. Innovations such as electronic medical records, telemedicine, and digital health applications have shifted the paradigm of traditional healthcare services towards a more integrated and technology-driven approach. However, this development poses significant legal challenges, particularly concerning personal data protection, the right to health, equitable access, and service accountability. This research aims to analyze the legal framework governing digital transformation in Indonesia's healthcare sector, evaluate its alignment with human rights and public health principles, and identify regulatory gaps that could hinder the achievement of an inclusive healthcare system. The method employed is a normative juridical approach, analyzing national legislation and international legal instruments related to health and information technology. The analysis reveals that despite the existence of foundational regulations, such as Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions, and Law Number 17 of 2023 concerning Health, there is still a need for regulatory harmonization and implementing policies focused on digital justice and the protection of vulnerable groups. This research recommends the establishment of a comprehensive legal framework that is adaptive to technological advancements and guarantees the constitutional right of every citizen to inclusive and equitable healthcare services.